Business Analysis of Selling and Buying Non-Fungible Tokens (NFT) at MarketPlace OpenSea according to The Perspective of Islamic Law: Analisis Bisnis Jual Beli Non Fungible Token (NFT) Pada MarketPlace OpenSea Menurut Perspektif Hukum Islam - Sundari, Sundari; Faiza, Siti Nur; Rahma , Lailatul (El-Qist: Journal of Islamic Economics and Business (JIEB), 2022)
Abstract: Non-Fungible Token is a digital asset in the form of a certificate of ownership of an artwork, such as photos, videos, songs, or games in virtual form. These digital assets are stored in the Blockchain. NFT is a derivative of cryptocurrency, and the difference is that crypto-assets such as Bitcoin are the same as physical money because they have an exchange rate and can be traded. Meanwhile, NFT does not have the exact exchange rate because of its unique nature. NFT opens new investment opportunities for investors in the country to market their work in the global market. Since the Ghozali everyday phenomenon, many people have started following Ghozali's steps by selling various kinds of NFTs in the form of selfie ID cards, pornographic content, and self-identity that contain elements of ḍarar. The study method in this research is case study qualitative phenomenology. This study aims to identify and analyze the business of buying and selling NFT on the opensea.io marketplace from an Islamic perspective. This study shows that the more people who can see the opportunities and gaps in the NFT business, the more people will be engaged in the NFT buying and selling business. Buy and sell NFT using cryptocurrency as an illegal commodity to trade because crypto-assets contain elements of gharar, ḍarar, and qimār. Even though the form of this NFT exists, when this NFT is transacted using Cryptocurrencies whose form does not exist, it can be said that this buying and selling transaction is invalid. Keywords: Buy and Sell; NFT; Opensea.io; Artwork.   Abstrak: NFT atau Non Fungible Token merupakan aset digital berupa sertifikat kepemilikan sebuah karya seni, seperti foto,vidio, lagu, atau game dalam bentuk virtual. Aset digital ini disimpan dalam blockchain. NFT merupakan turunan dari cryptocurrency, bedanya aset kripto seperti bitcoin sama halnya dengan uang fisik karena memiliki nilai tukar dan dapat diperdagangkan. Sedangkan, NFT tidak memiliki kesamaan nilai tukar karena sifatnya yang unik. NFT membuka peluang investasi baru bagi para investor di tanah air untuk memasarkan karyanya di pasar global. Semenjak fenomena Ghozali Everyday yang menjadikan foto selfinya sebagai NFT ramai diperbincangkan dimedia sosial banyak sekali yang mulai mengikuti jejak Ghozali menjual berbagai macam NFT dalam bentuk selfi KTP, konten pornografi, dan identitas diri yang mengandung unsur ḍarar (bahaya). Metode penelitian dalam penelitian ini ialah kualitatif studi kasus fenomenologi. Tujuan penelitian ini untuk mengetahui dan menganalisa bisnis jual beli NFT pada market place opensea.io dalam perspektif Islam. Hasil penelitian ini menunjukkan Semakin banyak masyarakat yang bisa melihat kesempatan dan celah dari bisnis NFT maka akan semakin banyak masyarakat yang bergerak dalam bisnis jual beli NFT Namun sangat disayangkan untuk saat ini NFT ditransaksikan menggunakan mata uang Cryptocurrency. Jual beli NFT menggunakan mata uang  crypto sebagai komoditi haram untuk diperdagangkan. Sebab aset cyripto mengandung unsur gharar, ḍarar, dan qimār. Sekalipun wujud dari NFT ini ada namun ketika NFT ini ditransaksikan menggunakan Cryptocurency yang wujudnya tidak ada maka bisa dikatakan transaksi jual beli ini tidak sah. Kata Kunci: Jual Beli; NFT; Opensea.io; Karya Seni.